Struktur Sintaksis Bahasa Madura dalam Al Qur'an Tarjamah Basa Madura Karya Jamaah Pengajian Surabaya - Solehodin; Musyarrofah (Department of Qur'an dan Hadith Faculty of Ushuluddin and Philosophy UIN Sunan Ampel Surabaya, 2023)
One way to understand the Qur’an is through its translation. Therefore, the demand for translated version of the Qur’an within the Muslim community is quite significant. Jamaah Pengajian Surabaya (JPS) endeavors to meet this need by translating the Qur’an into Madurese. This article examines the characteristics, structure and syntax of the Al Qur’an Tarjamah Basa Madura by JPS. By employing a qualitative method and descriptive analysis, this study uncovers several findings. Notably, the Al Qur’an Tarjamah Basa Madura by JPS is translated interpretatively (tafsīrīyah) rather than literally (lafẓīyah), which could facilitate reader’ comprehension of the verses. Furthermore, the translations utilize Latin alphabet letters without diacritical marks to represent Madurese phonetics, with only a few instances marked with two letters. From a structural and syntactical perspective, the translation sometimes adheres to the spelling convention of the Madurese language, while at other times it follows the original structure of the Qur’anic language.